Polycyclic aromatic hydrocarbons at fire stations: firefighters' exposure monitoring and biomonitoring, and assessment of the contribution to total internal dose - Klara Slezakova (2017)
This work characterizes levels of eighteen polycyclic aromatic hydrocarbons (PAHs) in the breathing air zone of firefighters during their regular work shift at eight Portuguese fire stations, and the firefighters' total internal dose by six urinary monohydroxyl metabolites (OH-PAHs). Total PAHs (Sigma PAHs) concentrations varied widely (46.4-428 ng/m(3)), mainly due to site specificity (urban/rural) and characteristics (age and layout) of buildings. Airborne PAHs with 2-3 rings were the most abundant (63.9-95.7% Sigma PAHs). Similarly, urinary 1-hydroxynaphthalene and 1-hydroxyacenaphthene were the predominant metabolites (66-96% Sigma OH-PAHs). Naphthalene contributed the most to carcinogenic Sigma PAHs (39.4-78.1%) in majority of firehouses; benzo[a]pyrene, the marker of carcinogenic PAHs, accounted with 1.5-10%. Statistically positive significant correlations (r >= 0.733, p <= 0.025) were observed between EPAHs and urinary Sigma OH-PAHs for firefighters of four fire stations suggesting that, at these sites, indoor air was their major exposure source of PAHs. Firefighter's personal exposure to PAHs at Portuguese fire stations were well below the existent occupational exposure limits. Also, the quantified concentrations of post-shift urinary 1-hydroxypyrene in all firefighters were clearly lower than the benchmark level (0:5 recommended by the American Conference of Governmental Industrial Hygienists.